2012
DOI: 10.1088/0031-8949/86/01/015803
|View full text |Cite
|
Sign up to set email alerts
|

Quantum key distribution with several intercept–resend attacks via a depolarizing channel

Abstract: The disturbance effect of a depolarizing channel on the security of the quantum key distribution of the four state BB84 protocol, with multiple sequential intercept-resend attacks of many eavesdroppers, has been studied. The quantum bit error rate and the mutual information are computed for an arbitrary number N of eavesdropper. It is found that the quantum error rate decreases when increasing the depolarizing parameter p characterizing the noise of the channel. For p<0.165, there exist, a special value tr p o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Eve intercepts the signal transmitted from Alice to Bob and measures it in a bases chosen based on her input (see Fig. 2) [18, 19]. Eve’s input e represents her guess of input of Bob’s input b for that particular round.…”
Section: Assumptions and Attacksmentioning
confidence: 99%
“…Eve intercepts the signal transmitted from Alice to Bob and measures it in a bases chosen based on her input (see Fig. 2) [18, 19]. Eve’s input e represents her guess of input of Bob’s input b for that particular round.…”
Section: Assumptions and Attacksmentioning
confidence: 99%
“…It has been proved that in real world conditions, where the channel depolarization cannot be ignored, BB84 should perform better than SARG04 [11]. Also in our previous work another attack type in the presence of several eavesdroppers via a depolarizing channel was studied [12].…”
Section: Introductionmentioning
confidence: 97%
“…The intercept-resend attack is approached on the quantum communication channel (Garapo et al, 2016). Another study found that the quantum error rate decreases when increasing the depolarizing parameter characterizing the noise of the channel after applying the disturbance effect of a depolarizing channel on the security of the QKD of the four-state BB84 protocol has been applied (Dehmani et al, 2012). Another paper presents a novel analytical model to investigate the eavesdropping attacks in wireless net of things; the results indicate that the probability of eavesdropping attacks heavily depends on the shadow fading effect, the path loss effect, Rayleigh fading effect, and the antenna models (Li et al, 2016).…”
Section: Introductionmentioning
confidence: 99%